Commonwealth action programme for the digital divide (Commonwealth Secretariat LondonGB, 2001)
Provides the overall conclusions and recommendations in Part 1. Identifies and discusses the key issues of information and communications technologies and how they could be used as a tool for development in the Commonwealth, and how the Commonwealth might address the growing digital divide.
Contents: Pt. 1. Report. -Pt. 2. Annexes